1992
DOI: 10.1139/z92-181
|View full text |Cite
|
Sign up to set email alerts
|

Prey selection in relation to insect availability by the common poorwill (Phalaenoptilus nuttallii)

Abstract: We determined the diet of common poorwills (Phalaenoptilus nuttallii) by analysing fecal samples collected from roost and nest sites in the Okanagan Valley of British Columbia. The two major insect orders present in the diet in 1989 were Coleoptera (47% by volume) and Lepidoptera (49%), which comprised only 15 and 3%, respectively, of the insects sampled using sticky traps in 1989. Based on the femur length of coleopterans consumed, all coleopterans eaten were longer than 6.7 mm (excluding the head), whereas 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…Twenty-two beetles ranging in body length from 2.4 to 28.1 mm were taken from light traps and used to develop the regression function for the relationship between claw Claw length described a significant amount of the variation in body length (r 2 = 0.74, F 1,21 = 56.80, P < 0.05), a result comparable to previous studies (e.g. Aldridge & Rautenbach, 1987; r 2 = 0.75; see also Csada, Brigham & Pittendrigh, 1992). Eighty-five beetle claws were extracted from the guano samples collected between 28 April and 30 June to determine the size of beetles eaten during the prematernity and maternity periods (Fig.…”
Section: Prey Sizesupporting
confidence: 79%
See 2 more Smart Citations
“…Twenty-two beetles ranging in body length from 2.4 to 28.1 mm were taken from light traps and used to develop the regression function for the relationship between claw Claw length described a significant amount of the variation in body length (r 2 = 0.74, F 1,21 = 56.80, P < 0.05), a result comparable to previous studies (e.g. Aldridge & Rautenbach, 1987; r 2 = 0.75; see also Csada, Brigham & Pittendrigh, 1992). Eighty-five beetle claws were extracted from the guano samples collected between 28 April and 30 June to determine the size of beetles eaten during the prematernity and maternity periods (Fig.…”
Section: Prey Sizesupporting
confidence: 79%
“…Aldridge & Rautenbach, 1987; r 2 = 0.75; see also Csada, Brigham & Pittendrigh, 1992). Eighty-five beetle claws were extracted from the guano samples collected between 28 April and 30 June to determine the size of beetles eaten during the prematernity and maternity periods (Fig.…”
Section: Prey Sizementioning
confidence: 99%
See 1 more Smart Citation
“…This makes for a natural comparison of prey selection by this species at the two locations. Csada, Brigham & Pittendrigh (1992) found that poorwills in the Okanagan selected lepidopterans (moths) and coleopterans (beetles) from the insects available. Further, poorwills only ate the largest beetles, suggesting that the birds preferred them.…”
Section: Introductionmentioning
confidence: 99%
“…Only moths, beetles and flies were considered in the analysis since these groups constitute > 95% of the diet (Csada, Brigham & Pittendrigh, 1992;Bayne & Brigham, 1994).…”
Section: Methodsmentioning
confidence: 99%